Construct validation of a multidimensional measure of perceptual–motor integration in young children - Esra Güven; Abdullah Furkan Cangi (Anatolian Journal of Health Research, 2026)
Aim: Perceptual and praxis skills are fundamental to adaptive functioning in early childhood. The aim of this study was to develop and examine the psychometric properties of the Perception and Praxis Scale (PPS), designed to assess sensory–motor integration across four domains: somatosensory, vestibular, visual, and motor planning. Methods: Data were collected from parents of 496 typically developing children aged 2–6 years. Sample adequacy and factorability were confirmed using the Kaiser–Meyer–Olkin measure and Bartlett’s test of sphericity. Construct validity was examined through exploratory factor analysis and confirmatory factor analysis. Reliability analyses included internal consistency, test–retest reliability, and item discrimination. Additional construct validity evidence was examined using composite reliability, average variance extracted, maximum shared variance, and heterotrait–monotrait ratios. Results: EFA revealed a four-factor structure accounting for 59.8% of the total variance, with factor loadings ranging from .46 to .83. CFA supported this structure and demonstrated acceptable to good model fit (χ²(1,028) = 2,210.20, χ²/df = 2.15, CFI = .94, TLI = .93, RMSEA = .047, SRMR = .049). Internal consistency coefficients were high (α = .86–.95; ω = .87–.95), and four-week test–retest reliability was excellent (ICC = .89, 95% CI [.84–.93]). All items showed strong discriminative power between the upper and lower 27% groups (p < .001).Conclusion: The PPS is a psychometrically robust instrument for assessing distinct yet related aspects of perceptual and praxis functioning, offering a culturally sensitive and time-efficient means to identify developmental differences and monitor progress in early childhood.